Bottle Design of Onion Chili Sauce using Kansei Engineering for SMEs in Indonesia - Weldellin Tanawi; Syafina Aisha Fitori; Rida Zuraida (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The SMEs industry in Indonesia keep growing significantly in the last 10 years, driven by digital channels such as e-commerce. One of Indonesia's popular food products is onion chili. However, the packaging design of the product is generic and may not be attractive or meet consumer expectations. This study aims to design the product packaging for onion chili using Kansei Engineering (KE) to increase its value. To aim for the objectives, this research was conducted in two stages, the first stage was to assess customer satisfaction and collected Kansei words that related to packaged onion chili. The satisfaction level was measured based on color, packaging durability, and packaging style. In the second stage, a questionnaire consisting of a packaged design checklist and Kansei words was developed. Then, the Kansei words were reduced using Principal Component Analysis (PCA) and obtained 3 main factors which are convenience, durability, and hygiene & attractiveness. The result was then followed by determining the elements of the new design based on Partial Least Square Regression (PLSR) and followed by design requirement analysis. Three proposed bottle designs were developed based on those 3 main factors as an alternative design for SMEs who sell this kind of product